SECURE ATTACHMENT DAN KUALITAS HUBUNGAN BERPACARAN PADA DEWASA AWAL YANG MENJALANI LDR - Anma Caeria Galuh Pramantari; Christiana Hari Soetjiningsih (Bajang Institute, 2023)
The focus of this study is to determine the relationship between secure attachment and relationship quality in early adulthood among college student who undergoing long distance relationship (LDR). This Study uses quantitative approach with correlational design. The sampling technique used is purposive sampling. The subject of this study is 44 SWCU Psychology Faculty Students Class of 2018 and 2019 who are undergoing long distance relationship. The measuring tools used in this study are adult attachment scale and perceived relationship quality – revised. Based on the correlation results of the product moment-Pearson is r = r = 0,348 (p < 0.05), meaning that hypothesis of this study is there is a positive relationship between secure attachment and relationship quality among college students who are undergoing long distance relationship (LDR).